The Narration of Convenient Public Services at the Sheikh Zayed Solo Grand Mosque in Online Media - Aji Kurniawan Ade Purwanto; Turnomo Rahardjo (Communication and Islamic Broadcasting Study Program, Faculty of Da'wah and Communication, Universitas Islam Negeri Sunan Kalijaga Yogyakarta, Yogyakarta, Indonesia, 2023)
This research attempts to examine the coverage of the Sheikh Zayed Grand Mosque in Solo in the online media Solopos.com. This study uses a qualitative-descriptive method and uses the narrative theory of the actan model developed by Algirdas Greimas. This research focuses on news text narratives collected through the online media Solopos.com after the Grand Mosque of Sheikh Zayed Solo was inaugurated. The results of this study found the structure of the meaning of reporting on the Sheikh Zayed Solo Grand Mosque on Solopos.com which displays the positive side of reporting about the mosque. This positive news is related to parking, security, and shuttle service at the Grand Mosque of Sheikh Zayed Solo.